A Dose of Public Health through Grassroots Advocacy: The Development of Tobacco-Control Policy on a College Campus - Bryant, G. (Maine Policy Review, 1999)
Maine has the unfortunate distinction of having the highest rate of tobacco use among 18- to 30-year-olds of any state in the nation. Moreover—as Bryant points out—first-time smoking among traditional college-age populations has risen nearly 30 percent in the past decade. Armed with these statistics, it is not difficult to conclude that college campuses in Maine face a serious public health issue. Carried by the momentum of recent tobacco-control policy developments at the state level, the University of Maine at Farmington (UMF) has passed a stringent new tobacco-control policy that places UMF in the forefront of nationwide efforts to curb tobacco use among college-age students, and also to minimize the harmful effects of secondhand smoke. In this article, Bryant traces the grassroots advocacy efforts that led to the recent passage of a new tobacco-control policy at UMF. She concludes with a set of recommendations for policy advocates in other settings.